Cytotoxic lignans from the stems of Styrax camporum (Styracaceae) - Teles, Helder L. [UNESP]; Hemerly, J. P.; Pauletti, Patrícia M. [UNESP]; Pandolfi, José R. C. [UNESP]; Araujo, Angela Regina [UNESP]; Valentini, Sandro Roberto [UNESP]; Young, M. Cláudia M.; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce H. S. [UNESP] (Taylor & Francis Ltd, 2005)
An ethanolic extract from the stems of Styrax camporum Pohl (Styracaceae), a plant traditionally used for gastrointestinal diseases, was fractionated and subjected to flash chromatography and afforded two benzofuran lignans, egonol and homoegonol, and one furofuran lignan, (+/-) syringaresinol, which were identified by spectral data interpretation. Their cytotoxic activities against Hep-2 (larynx epidermoid carcinoma), HeLa (human cervix carcinoma) and C6 (rat glioma) cell lines were evaluated using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay at several concentrations for 24 h. Activities could be observed for egonol against C6 (IC50 = 3.2 mu g/mL) and Hep-2 (IC50 = 3.6 mu g/mL) cell lines, and for homoegonol against C6 (IC50 = 4.9 mu g/mL) and HeLa (IC50 =- 5.3 mu g/mL) cells.
Keywords: Styrax camporum; Styracaceae; cytotoxic lignans; MTT assay